Preventing risk situations at type-ii diabetes mellitus patients through continuous glucose monitoring and prediction-based teleconsults - Nieto Chaupis, Huber (2015)
We present a scheme of eHealth based on teleconsults aimed to reduce unexpected events and complications in type-2 diabetes mellitus (DM-II). To this end, this study has considered the history of glucose tests taken as input inside a predictive mathematical scheme based on probabilities. The resulting output goes to a real-time monitoring system in order to detect and update those cases where patients would require of rapid assistance. The simulations have shown that the opportune intervention of teleconsults might be effective in the sense of monitoring diet and drug-based treatment by employing simple mobile phones and minimal software applications. For example, the case of a critic patient with a rapid increasing of glucose above 200 mg/dL, the opportune intervention of teleconsults might reduce these values by a 50% during a time of 20±2 days. It can also be traduced as the improvement on the stability of patient against the risk of cardiovascular events, or others DM-II inherent complications.